SEG Technical Program Expanded Abstracts 2012 2012
DOI: 10.1190/segam2012-0763.1
|View full text |Cite
|
Sign up to set email alerts
|

Development of a downhole sparker source with adjustable frequencies

Abstract: We report on the discovery and testing of a downhole sparker source that is able to generate acoustic signals with peak frequencies from 2 to 1000 Hz. The sparker can be configured such that the energy of the produced acoustic signals lies within a spectral band that is suitable for transmission lengths of the order of thousands of feet, making it a viable source for single-well imaging and reverse vertical seismic profiling. The sparker produces repeatable shots and allows a firing rate much less than typical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Using transient sources (e.g., sparker, Heighl et al . ) requires the precise knowledge of the trigger start time. Swept sources (Kolle and Theimer ) require recording reference pilot signals with methods similar to drill‐bit SWD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using transient sources (e.g., sparker, Heighl et al . ) requires the precise knowledge of the trigger start time. Swept sources (Kolle and Theimer ) require recording reference pilot signals with methods similar to drill‐bit SWD.…”
Section: Discussionmentioning
confidence: 99%
“…; Heigl et al . ). In this context, seismic while drilling (SWD) using the working drill bit as a downhole source is a known tool providing reverse vertical seismic profiling (reverse VSP or RVSP) information at relatively low cost along with large configurations of surface seismic sensors (Poletto and Miranda ).…”
Section: Introductionmentioning
confidence: 97%
“…It has been suggested that a sparker could be designed to maximise the energy in the desired frequency range (Brizzolara et al, 2003(Brizzolara et al, , 1999. It appears that control over the peak acoustic frequency generated by a sparker may be able to be achieved by controlling parameters such as capacitance, which affects the pulse length (Brizzolara et al, 1999;Heigl et al, 2012;Paillet, 1984).…”
Section: Acoustic Sparkersmentioning
confidence: 97%
“…Usually water, or salty water, is used as a medium of transforming the shock wave. [12] found that when the electric energy was discharged through the liquid, it produced heat, which almost instantaneously vaporized the surrounding fluid and a vapor bubble of high pressure and temperature were formed. This vapor bubble gave rise to a pressure shock wave within the liquid.…”
Section: Electrohydraulic Forming Process (Ehf)mentioning
confidence: 99%